# Solve for: 414 Request-URI Too Large

## Expression: $\left\{\begin{array} { l } -3=3y-\frac{ 3 }{ 4 }x \\ 3x=2y-8\end{array} \right.$

Simplify the expression

$\left\{\begin{array} { l } -3x+12y=-12 \\ 3x=2y-8\end{array} \right.$

Move the variable to the left-hand side and change its sign

$\left\{\begin{array} { l } -3x+12y=-12 \\ 3x-2y=-8\end{array} \right.$

Sum the equations vertically to eliminate at least one variable

$10y=-20$

Divide both sides of the equation by $10$

$y=-2$

Substitute the given value of $y$ into the equation $3x-2y=-8$

$3x-2 \times \left( -2 \right)=-8$

Solve the equation for $x$

$x=-4$

The possible solution of the system is the ordered pair $\left( x, y\right)$

$\left( x, y\right)=\left( -4, -2\right)$

Check if the given ordered pair is the solution of the system of equations

$\left\{\begin{array} { l } -3=3 \times \left( -2 \right)-\frac{ 3 }{ 4 } \times \left( -4 \right) \\ 3 \times \left( -4 \right)=2 \times \left( -2 \right)-8\end{array} \right.$

Simplify the equalities

$\left\{\begin{array} { l } -3=-3 \\ -12=-12\end{array} \right.$

Since all of the equalities are true, the ordered pair is the solution of the system

$\left( x, y\right)=\left( -4, -2\right)$

Random Posts
Random Articles